Remarks at the Council of Foundations - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed the issues that link the United States to other countries: health, migration, trade, peace and stability, energy, food, and crime and narcotics. The responsibilities of foundations do not end with our cities and communities. The job the Bank does can only be done on the basis of partnership with the governments, with the other multilateral institutions, with the private sector, but most particularly with civil society. It is crucial that the foundation organizations in the country that have the experience, that know about volunteerism, about taking things in their own hands, diversity of interests, different points of view, and experience, should come together on the global issues.